2009
DOI: 10.1002/pola.23617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an anionic monomer on the pickering emulsion polymerization stabilized by titania hydrosol

Abstract: Polystyrene (PS) nanocomposite particles with high titania content are prepared by Pickering emulsion polymerization. A self‐made titania hydrosol modified by an anionic monomer sodium styrene sulfonate (NaSS) is used as a stabilizer and photocatalyst. The stability of the emulsion system is greatly improved by the electrostatic interaction between negatively charged NaSS and positively charged titania nanoparticles. The nanocomposite spheres with the diameter of around 120 nm are highly charged, indicating ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 41 publications
2
36
1
1
Order By: Relevance
“…Song and coworkers performed photocatalytic emulsion copolymerizations of styrene and EGDMA with auxiliary monomers of acrylic acid or sodium styrene sulfonate, and in the presence of a cationic titania hydrosol. They found that the auxiliary monomers greatly promoted adhesion of the titania nanoparticles onto the polymer latexes [125,126].…”
Section: Assembly Of Nanoparticles Onto the Surface Of Polymermentioning
confidence: 99%
“…Song and coworkers performed photocatalytic emulsion copolymerizations of styrene and EGDMA with auxiliary monomers of acrylic acid or sodium styrene sulfonate, and in the presence of a cationic titania hydrosol. They found that the auxiliary monomers greatly promoted adhesion of the titania nanoparticles onto the polymer latexes [125,126].…”
Section: Assembly Of Nanoparticles Onto the Surface Of Polymermentioning
confidence: 99%
“…However other inorganic fillers, such as zinc oxide [40,41], magnetite [42], graphene [43,44] or cerium dioxide [51] have also been used. The use of titania NPs as Pickering stabilizers is scarce [30,[45][46][47][48]52] and to the best of our knowledge none of these works have used titania NPs to stabilize film forming latexes for coating applications. Therefore, the photocatalytic efficiency of films cast form waterborne dispersions Pickering stabilized with TiO 2 remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 96%
“…These advantages have attracted the attention of the polymer community in the last years and a wide range of hybrid colloidal materials have been synthesized by means of emulsion [21,29,[37][38][39][40][41][42][43][44][45][46][47][48] or miniemulsion polymerization [31,32,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…By far, many excellent works have been done on the issue of Pickering emulsions. However, most of these works deal with emulsions having internal phase levels below 70 vol% [10,11]. Recently, Arditty et al [12] described silicone oil-in-water pickering emulsions with up to 90 wt% internal phase and water-in-silicone oil pickering emulsions having internal phase of up to 75 wt% stabilized by hydrophilic silica particles and silanized hydrophobic silica particles, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Particle-stabilized emulsions, also known as Pickering emulsion, seem a good choice to prepare polyHIPEs without surfactants [10,11]. By far, many excellent works have been done on the issue of Pickering emulsions.…”
Section: Introductionmentioning
confidence: 99%